ANALISIS PERFORMA ATLET DENGAN MENGGUNAKAN TEKNOLOGI GNSS - Lazuardi Z Soeharno, Dzikry
Athlete's ability development can be conducted by assessing athlete's performance. The problem is there are few athlete's performance parameters which can not be easily gained. There are few athlete's performance parameters requiring position data thus GNSS (Global Navigation Satelite System) can be used. This research aimed to analyze athlete's performance using one of GNSS which is GPS (Global Positioning System). GPS Tracking device will be placed to athlete's body while they are doing physical activity. GPS will be producing position data in certain period of time which are used to generate parameter needed in analyzing athlete performance. The emphasis of this research are acceleration, maximum speed, speed endurance, optimum speed, agility, quickness, aerobic endurance, anaerobik endurance, spesific endurance, maximum strength, strength endurance, and power. Data acquisition is conducted to two athletes which are running around the running track and spesific test for few parameters. Data obtained are position, time series, and speed during the running activity. Analysis is conducted to know how GPS Tracking data can support athlete performance assessment. The result of analysis shows that parameters generated by GPS Tracking device are acceleration, maximum speed, speed endurance, optimum speed, agility, aerobic endurance, anaerobic endurance, spesific endurance, and power. The result of those parameters are used to analyse athlete's performance. Quickness needs better sampling rate. Maximum strength and strength endurace are not requiring position thus GPS Tracking deviced can not obtain those parameters.